Experimental and computational studies of fluid structure interaction of tsunami bore on coastal bridges / Iman Mazinani - Iman , Mazinani (2021)
To understand the potential effect of the tsunami forces on coastal bridges due to tsunami bore, a series of experimental tests were conducted, and results were compared to those calculated with a fluid-structure interaction (FSI) analysis. Various wave heights and shallow water were utilized in the experiments and computational process. Nine types of 1:40 scale concrete bridge models were placed in a mild beach profile to a 24 m × 1.5 m × 2 m wave flume for the experimental investigation. An Arbitrary Lagrange Euler (ALE) formulation was developed for the propagation of tsunami solitary and bore waves by an FSI package of LS-DYNA using a high-performance computing (HPC) system. The results showed that the fully coupled FSI models could plausibly capture the tsunami wave forces for all ranges of wave heights and shallow depths. It was identified that after ~1.4 s, the wave elevation could potentially reach it's maximum (here, 0.35-0.4 m), which was in good agreement with the results calculated by the Weigel model. Likewise, the Bore height increased with an increase in the wave height, reaching ~0.22 m at a wave height of 0.38 m. The horizontal force reached 180 N after 7.3 seconds and then gradually decreased approaching zero after 8 seconds. The effects of the overturning moment, horizontal force, uplift, and impact force on the pier and deck of the bridge were evaluated. The presence of girders, on a model of a bridge deck with girders, is studied by making a direct comparison by changing the number of girders on the model. It appears that the girders have a significant influence on the uplift and overturning moment. Increasing the number of girders on bridge models significantly increased uplift and overturning moments. However, this variation depended on wave conditions and shallow water. The effect of four different baffle plates on the mitigation of tsunami force is investigated. The result indicated the full baffle plate reduced horizontal and uplift force up to 40 %.